Low Cost Walk-in Type Seed Germinator - Kumar, Adarsh; Gupta, B. N.; Verma, K. K. (Indian Forester, 1980)
A simplified plan for a low cost walk-in type seed terminater is given. This germinator has heen designed and fabricated in this Institute with the locally available material. The germinator has been tested and found satisfactory for use, throughout the year, from 18°C to 35°C (± 10C) temperature. In all two hundred and sixteen germination trays of 46×30 cm size each can be arranged, at a time, for conducting germination tests.